Cepheid xpert monitor platform for the confirmation of BCR-ABL1 IS conversion factors for the molecular monitoring of chronic myeloid leukaemia. (October 2016) - Gerrard, Gareth; Foong, Hui En; Mudge, Katherine; Alikian, Mary; Apperley, Jane F.; Foroni, Letizia
Highlights: We implemented an International Scale Conversion Factor verification step for CML. Used International Scale reporting Cepheid Xpert BCR-ABL cartridges. Can help decide to accept or retest change in CF for use in long-term monitoring. Abstract: Molecular monitoring of BCR-ABL1 expression in chronic myeloid leukaemia (CML) is well established. As the International Scale (IS) normalised BCR-ABL1/ABL1 ratio at 3 months post-treatment is now an important milestone in patients' treatment schedule, the reliable and reproducible measurement of BCR-ABL1 levels is therefore paramount. IS conversion factors (CF) are established via sample exchange and yearly ratification with an external reference laboratory. Since any change to an established IS CF could lead to discontinuity in longitudinal results, we wished to add an internal verification step as an additional safeguard. We used the Cepheid GeneXpert qPCR and IS calibrated Xpert BCR-ABL Monitor cartridge system, parallel to our in-house pipeline on 50 CML samples, over the period of one week to verify the CF for those samples and compare it to the externally provided CF. The median non-IS in-house BCR-ABL1/ABL1 values were significantly different than that from the IS GeneXpert, but they became non-significant when adjusted to CF provided by the CXM and by the current external CF, validating it. These metrics can help decide to accept or reject an updated CF value, especially where a significant change in CF might lead to a discontinuity in ongoing patient monitoring.